2022
DOI: 10.1186/s12889-022-12492-7
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the 2018 Japan Floods on long-term care insurance costs in Japan: retrospective cohort study

Abstract: Background Climate change has increased the frequency and severity of torrential rains and floods around the world. Estimating the costs of these disasters is one of the five global research priorities identified by WHO. The 2018 Japan Floods hit western Japan causing extensive destruction and many deaths, especially among vulnerable elderly. Such affected elderly would need long-term care due to the various health problems caused by the disaster. A Long-Term Care Insurance (LTCI) system provid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 44 publications
1
8
0
Order By: Relevance
“…The WHO has noted that the problem of healthcare costs is vital to building a healthcare system that is resilient against climate change, and there are few estimations of these costs [ 35 ]. We have already shown the change in costs of long-term care insurance for older victims of this disaster [ 17 ]. Putting these results together, we can provide a more comprehensive account of health-related cost changes for the victims.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The WHO has noted that the problem of healthcare costs is vital to building a healthcare system that is resilient against climate change, and there are few estimations of these costs [ 35 ]. We have already shown the change in costs of long-term care insurance for older victims of this disaster [ 17 ]. Putting these results together, we can provide a more comprehensive account of health-related cost changes for the victims.…”
Section: Discussionmentioning
confidence: 99%
“…1223-2). Using this dataset, it was found that the victims used more of several types of medicines than non-victims [14][15][16][17].…”
Section: Data Sourcementioning
confidence: 99%
See 3 more Smart Citations